Before we can factor the equation, let's convert first it into a general form of a quadratic equation ax² + bx + c = 0 where "x" is a variable. See the steps below.
Subtract 8b² and 2 on both sides of the equation.
![23b^2-49b+26-8b^2-2=8b^2+2-8b^2-2](https://img.qammunity.org/2023/formulas/mathematics/college/m5zk8lckbr1ytsl2x91z6dxvclr2aiumop.png)
Arrange the terms in terms of their degree.
![23b^2-8b^2-49b+26-2=8b^2-8b^2+2-2](https://img.qammunity.org/2023/formulas/mathematics/college/7icu8vgph6jtxz25hmf58tcphzq3sjwnba.png)
Combine similar terms.
![15b^2-49b+24=0](https://img.qammunity.org/2023/formulas/mathematics/college/3evj00m9hkx0mmrtpnaatai0ewifnzrp4r.png)
We have converted the equation into its general form and that is 15b² - 49b + 24 = 0.
Let's now factor this equation using the Slide and Divide Method.
1. Slide the leading coefficient 15 to the constant term 24 by multiplying them.
![15*24=360](https://img.qammunity.org/2023/formulas/mathematics/college/pqhkr0vgjs8odt58zuf136qu5b32s2ibiw.png)
Upon sliding, the equation now becomes:
![b^2-49b+360=0](https://img.qammunity.org/2023/formulas/mathematics/college/6bgdybl06dmeeumc87i1c7p288816bkrrw.png)
2. Let's find the factors of 360 that sums up to -49.
• 6 and 60 → sum is 66
,
• 8 and 45 → sum is 53
,
• 9 and 40 → sum is 49
,
• -9 and -40 → sum is -49
Therefore, the factors of 360 that sums to -49 are -9 and -40.
Hence, the equation b² - 49b + 360 can be factored into:
![(b-9)(b-40)=0](https://img.qammunity.org/2023/formulas/mathematics/college/gm6aw6lwivwjwufqg7vhc7w1mydzk0xcp5.png)
3. Since we slide 15 earlier, divide the factors -9 and -40 by 15 by simplifying the fraction.
![-(9)/(15)\Rightarrow-(9/3)/(15/3)=-(3)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/uy9okop1h72or9o32sz5r5cn4bons0c1lb.png)
![-(40)/(15)\Rightarrow-(40/5)/(15/5)=-(8)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/cuv6l7nipi6y82okmzbebhvbjfp1qfzpve.png)
4. To find the factors of the equation, simply slide the denominator in each factor to b.
![\begin{gathered} (b-(3)/(5))\Rightarrow(5b-3) \\ (b-(8)/(3))\Rightarrow(3b-8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6za6f6z8wq0imk5mwsa0qs0ccgekowhuyy.png)
The factors of the equation are (5b - 3)(3b - 8).
Let's now solve for b. Simply equate each factor to zero and solve for b.
![\begin{gathered} 5b-3=0 \\ 5b=3 \\ b=(3)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jchoexm37vwzdqmdncfhbht96jg1phi2wk.png)
![\begin{gathered} 3b-8=0 \\ 3b=8 \\ b=(8)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zh13b5nkjg6ogggl51q3gkxl5l6c18j9sw.png)
ANSWER:
The factors of the equation are (5b - 3)(3b - 8) and the values of b are 3/5 and 8/3.